Gastroretentive drug delivery systems - a review - CHIRAG CHUGH,; ARUN NANDA, (International Journal of Pharma and Bio Sciences, 2017)
This review is an attempt to discuss various pharmaceutical techniques which improve the gastric residence time (GRT). Gastroretentive drug delivery systems (GRDDS) are fabricated for increasing the gastric emptying time and release the drug at predetermined rate. These systems are often designed for improved drug dissolution in gastric fluid which may enhance the drug absorption in the upper tract of gastrointestinal tract (GIT) and improve the bioavailability of the drugs. In GRDDS various approaches have been used for instance, hydrodynamically balanced systems, floating drug delivery systems, bioadhesive systems, raft systems, magnetic systems, swelling and expanding systems. This review also summarizes the mechanism, advantages and limitations along with the recent advances and application areas of such GRDDS.